A review of failures of railway monoblock prestressed concrete sleepers. (July 2022) - Henrique de Souza Lima, Eros; Manoel Pereira Carneiro, Arnaldo
Highlights: Review of the literature state of the art of the main deterioration mechanisms of prestressed concrete sleepers. Analysis of causes and consequences of failures in prestressed concrete sleepers. Current practices to prevent and mitigate prestressed concrete sleeper failures are provided. Abstract: Prestressed concrete sleepers are being increasingly used for modern railways worldwide. The main advantages of this type of sleeper are its high mechanical strength, stability, and durability. However, there are challenges in ensuring that the prestressed concrete sleepers meet expected performance standards, as many concrete sleepers fail prematurely and need to be replaced every year. Such failures have already been responsible for large-scale railway accidents which have caused financial losses and endangered the safety of rail transport users. This paper proposes to review the current literature on the main deterioration mechanisms of prestressed concrete sleepers, discuss their causes and consequences, and suggest the main corrective and preventive measures that can be taken to minimize each problem. For ease of understanding, the failures have been separated into two groups: intrinsic failures, such as failures due to internal concrete deficiencies, and extrinsic failures, such as those associated with the high impact loads of railways and freeze–thaw cycles. In general, prestressed concrete sleeper failures manifest as cracking; the position and form of which is a good indication of the type of degradation. The causes of sleeper failures are almost always related to the poor maintenance of railroad tracks, poor conditions of the rolling stocks, and the use of inappropriate materials in the production of concrete, such as reactive aggregates.